2021
DOI: 10.4314/ajcem.v22i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics and antibiogram profile of Escherichia coli O157:H7 isolated from raw and fermented (nono) milk in Benin City, Nigeria

Abstract: Background: Most Escherichia coli strains are harmless commensals, but some serotypes can cause serious food poisoning in their hosts, and are infrequently responsible for product recalls due to food contamination. The present study was carried out to determine the occurrence of E. coli O157:H7 and other E. coli strains from raw and fermented (nono) milk in Benin City, Nigeria.Methodology: A total of 66 (33 raw and 33 nono) milk samples were obtained from retailers from 3 different stations in Aduwawa market, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
3
3
1
Order By: Relevance
“…Moreover, high percentages of the isolates (92.0%) were also resistant to Erythromycin. The total resistance to Penicillin G was similar to the reports of Igbinosa and Chiadika [110] and Reuben et al [111] Jimma towns, respectively. The 96.0% sensitivity to Tetracycline was consistent with Haile et al [114] in Jimma, Bekele et al [10] in Addis Ababa, Osaili et al [113] in Amman City (Jordan), and Bedasa et al [19] in Bishoftu town who reported 100%, 100.0%, 100.0% and 97.5% sensitivity to Tetracycline.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, high percentages of the isolates (92.0%) were also resistant to Erythromycin. The total resistance to Penicillin G was similar to the reports of Igbinosa and Chiadika [110] and Reuben et al [111] Jimma towns, respectively. The 96.0% sensitivity to Tetracycline was consistent with Haile et al [114] in Jimma, Bekele et al [10] in Addis Ababa, Osaili et al [113] in Amman City (Jordan), and Bedasa et al [19] in Bishoftu town who reported 100%, 100.0%, 100.0% and 97.5% sensitivity to Tetracycline.…”
Section: Discussionsupporting
confidence: 87%
“…However, no E. coli O157 was detected among SN-F E. coli isolates from chickens in Jos Plateau State, Northcentral Nigeria [17]. The absence of E. coli O157 in cattle in this study contrasts previous reports in cattle/dairy products sampled in Northcentral Nigeria in which phenotypic E. coli O157 prevalence ranged from 0.43-67.5% [13,19,20,28] and in Southsouth Nigeria where 6.94-28% E. coli O157 prevalence rate was reported [18,29]. In Southwestern Nigeria, phenotypic E. coli O157 prevalence rate reported in cattle/beef ranged from 3.9-28% [23,30].…”
Section: Discussioncontrasting
confidence: 83%
“…coli / E. coli O157 isolates from food animals, meat and associated products in Nigeria [21, 23, 29, 30] and other countries [14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations